2017
DOI: 10.1209/0295-5075/117/40003
|View full text |Cite
|
Sign up to set email alerts
|

Cluster mean-field analysis for spontaneous symmetric breaking in a bidirectional two-lane system with narrow entrances and parallel update

Abstract: This paper carries out a cluster mean-field analysis for spontaneous symmetric breaking in a two-lane asymmetric exclusion process with narrow entrances and parallel update. We demonstrate that the asymmetric low-density/low-density phase does not exist, based on a current minimization principle. With the increase of the cluster number in the cluster mean-field analysis, an exponential decay of the boundary between asymmetric high-density/low-density phase and symmetric low-density phase as well as the bulk de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Those theoretical analyses all indicated that the asymmetric phase does not exist. [22,23] However, the mechanism of the occurrence of SSB is still not well understood. [15] Yuan et al [18] investigated another two-lane TASEP.…”
Section: Introductionmentioning
confidence: 99%
“…Those theoretical analyses all indicated that the asymmetric phase does not exist. [22,23] However, the mechanism of the occurrence of SSB is still not well understood. [15] Yuan et al [18] investigated another two-lane TASEP.…”
Section: Introductionmentioning
confidence: 99%
“…It means that the density of the upstream of the intersection site of the northbound lane is larger than that of the eastbound lane, i.e., ρ 2 − ρ 1 > 0. The flow rate of the downstream of the intersection site of the northbound lane is smaller than that of the eastbound lane, i.e., J 4 − J 3 < 0 [37,38]. Therefore, the asymmetric phase exists when 0 < β < β c , see fig.…”
mentioning
confidence: 98%